Drugs for Alzheimer’s Disease from Salix Alba Discovered Computationally Utilizing Virtual Screening and Docking against 1b41 Protein - Sakshi Chaudhary; Samiksha Bhor (International Journal of Genetic Modifications and Recombinations, 2023)
Objective : The of this research is to evaluate the feasibility of using molecular docking techniques to identify novel acetylcholinesterase, a key enzyme implicated in the pathogenesis of Alzheimer’s disease, a neurodegenerative disorder with a gradual but steady progression to death, due to the gradual accumulation of beta-plaques and neurofibrillary tangles, as well as a decline in acetylcholine levels. Due to its function in converting acetylcholine into acyl and choline molecules, acetylcholinesterase is an enzyme that could potentially be the target of future Alzheimer's disease treatments. Methods: In the current research, findings of an in-silico study were examined or developing a novel remedy to combat AD. IMPPAT database was employed to retrieve the phytocompounds from Salix alba. Then the chosen molecules were screened on SwissADME for drug-likeness. Pyrx software was used for the final screening, which revealed the binding affinity between the ligands and the 1b41 target protein. 3d and 2d interactions were examined using Biovia and ligplus respectively. Results: Potential drug candidates for blocking the acetylcholinesterase enzyme include amentoflavone, astragalin, fragile, and salidroside. Conclusion: According to Lipinski's parameters, none of the compounds are violated (amentoflavone, astragalin, fragile, and salidroside), rendering them all suitable for inhibition activities against the AChE enzyme in AD.
Keywords: ADME analysis; Acetylcholine; Acetylcholinesterase; Alzheimer's Disease; Lipinski rule of 5; Salix alba; molecular docking